Estudo do reforço de edifícios em alvenaria resistente por perfis metálicos - Araújo, Adelmo Siqueira (2010)
One can estimate that there are approximately six thousand four storey residential box-type buildings in Recife Metropolitan Region which presents structures in risk situation. Among those buildings, twelve collapsed spontaneously, thirteen were demolished and in many others it was observed serious pathologies that demanded restrictions to their occupation. This work presents a methodology to deal with this problem, contemplating technical aspect as well as risks issues. One expects to eliminate the stigma of these buildings and to contribute to give dignity and security back to their inhabitants through a work that must be done based on technical and scientific concepts accepted worldwide in structural engineering. The solution to the problem consists of a proposal to create a steel structure to be installed in such building that, in case of collapse of their support walls, should carry all loads that act on them. This solution was modeled and designed using a software called Metálica 3D, showing results that assure security to all load cases that usually act in this type of structure. One expects that the proposed solution can generate significant social impact, due to the occurrence of several accidents with this type of buildings constructed with non structural bricks carrying loads beyond its own weight